The Clinical Relevance of Psammoma Body and Hashimoto Thyroiditis in Papillary Thyroid Carcinoma: A Large Case-control Study. Issue 44 (November 2015) - Cai, Ye-Feng; Wang, Qing-Xuan; Ni, Chun-Jue; Guo, Gui-Long; Li, Quan; Wang, Ou-Chen; Wu, Liang; Du, Hai-Yan; You, Jie; Zhang, Xiao-Hua
Abstract : Abstract: This study aims to investigate the impact of psammoma body (PB) on papillary thyroid carcinoma (PTC), and evaluate the association among PB, Hashimoto thyroiditis (HT), and other clinicopathologic characteristics in PTC patients. We conducted a retrospective case-control study involving 1052 PTC patients who underwent total thyroidectomy or lobectomy with lymph node dissection. Psammoma body was observed in 324 out of 1052 PTC (30.8%) patients. Ultrasonographic (US) calcification ( P < 0.001), multifocality of the tumor ( P = 0.047), lymph node metastasis (LNM) ( P < 0.001), HT ( P < 0.001), and Primary tumor (T), Regional lymph nodes (N), Distant metastasis (M) staging ( P = 0.001) were significantly related to the presence of PB. The presence of PB was significantly associated with US microcalcification ( P < 0.001). In the subgroup with HT, compared with the patients without PB, the patients with PB exhibited a higher frequency of central LNM (54.7% vs 32.1%; P < 0.001) and US microcalcification (94.7% vs 38.8%; P < 0.001), as well as smaller tumors (0.9 ± 0.6 vs 1.3 ± 0.9 cm; P < 0.001). In the subgroup without HT, the patients with PB displayed a higher incidence of lateral LNM (25.8% vs 14.6%; P < 0.001), US microcalcification (87.3% vs 52.5%; P < 0.001), and extrathyroidal extension (47.2% vs 34.8%; P = 0.001), as well as larger tumors (1.3 ± 0.9 vs 1.0 ± 0.8 cm; P < 0.001) than without PB. Moreover, in the subgroup with PB, the PTC patients with HT showed a higher LNM (77.9% vs 57.2%; P < 0.001) and a lower frequency of extrathyroidal extension (20.0% vs 47.2%; P < 0.001) than without HT. Psammoma body is a useful predictor of aggressive tumor behavior in PTC patients. HT with PB shows more aggressive behaviors than non-HT with PB in PTC patients.